Kenya’s Climate-Smart Agriculture Investment Plan unlocks over US$ 1 Million climate finance, benefitting 60,000 community members - Jalango, Dorcas; Mundia, Caroline; Nguvi, Caroline (2025)
The Alliance of Bioversity-CIAT - AICCRA project led the development of 22 climate resilience projects under the World Bank’s Financing Locally Led Climate-Action program, collaborating with the Siaya County Government, International Water Management Institute and Kenya’s Ministry of Agriculture – Climate Change Unit. Using Kenya’s Climate-Smart Agriculture Investment Plan, 39 county staff and community members were trained in developing bankable proposals, and on investment readiness. This effort secured US$1.025 million climate finance, benefitting 60,000 community beneficiaries, through initiatives focused on boosting food security, income, and sustainable livelihoods.